2021
DOI: 10.1111/soin.12429
|View full text |Cite
|
Sign up to set email alerts
|

The Body, The Self: How Women Ex‐Offenders in a Re‐Entry Program Negotiate Gendered, Embodied Identities, and the Implications for Desistance

Abstract: Existing scholarship posits that gender is socially constructed, with meanings attributed to bodies that signify conventions of masculinity and femininity. Such embodied constructs are integral to self and identity, though these meanings can be negotiated and fluid. Recent criminological work has found that changes in identity are essential to desisting from crime and that desistance processes are gendered. Yet little extant literature has examined how gendered, embodied identities play a role in the lived exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Through constructing new self-narratives, scholars have suggested, criminalised individuals may strive to reinterpret past events, interactions, actors, identities and capacities, and may re-frame their core self as inherently good, accountable, and active (Dewey et al. 2018; King 2013; Maruna and Liem 2021; Wesely 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Through constructing new self-narratives, scholars have suggested, criminalised individuals may strive to reinterpret past events, interactions, actors, identities and capacities, and may re-frame their core self as inherently good, accountable, and active (Dewey et al. 2018; King 2013; Maruna and Liem 2021; Wesely 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have also found that such narrative-making may involve a reaction to or engagement with ‘external’ accounts. Those accounts may be constructed by courtroom or other actors (e.g., judges, prosecutors, probation officers, prison therapists) that ‘co-author’ and re-construct individuals’ past, present or future narratives (Laws 2022; Maruna and Liem 2021; Quinn and Goodman 2022; Wesely 2022). The narratives take shape in a dynamic process ‘on an interactive basis embedded in particular context’ (Dollinger and Heppchen 2019: 317).…”
Section: Literature Reviewmentioning
confidence: 99%